PENGARUH MODEL PEMBELAJARAN SIKLUS BELAJAR SECARA DARING TERHADAP HASIL BELAJAR EKONOMI SISWA KELAS XI SEMESTER GANJIL DI SMAN 1 TRIMURJO LAMPUNG TENGAH TAHUN 2020 - Syukri, Nur Fitria; Aprilia, Rika; Rahayu, Dwi (Jurnal Elastisitas: Kajian Pendidikan Ekonomi, Ilmu Ekonomi, dan Kewirausahaan, 2020)
The problems that occur in the field can be identified as follows: The learning outcomes of class XI high school students in Economics subjects are still low, application The online learning cycle learning model has never been used in the learning process. The purpose of this study was to determine whether there was an effect of the online Learning Cycle learning model on the economic learning outcomes of the odd semester XI class students at SMAN 1 Trimurjo in 2020. In this study the authors used an experimental method. Data analysis using statistical formulas. The population in this study were all students of class XI SMAN 1 Trimurjo which consisted of 13 classes with a total of 466 students. Samples were taken using cluster random sampling technique. The instrument in this study used a multiple choice test. Data analysis used simple statistical analysis with the formula ttes.Based on the results of the calculation of hypothesis testing that has been done by the author, it is obtained thit = 4.58 and from the distribution table at the 5% level it is obtained ttab = 2.00 and so it is proven that thit> tdaf. Thus it can be concluded that "there is an effect of the Online Learning Cycle learning model on the economic learning outcomes of class XI students in the odd semester of SMAN 1 Trimurjo in 2020"